Establishing foundations: Designing a long-term experiment to evaluate whether nestboxes assist population recovery of an endangered species after fire - Jenna C.H. Ridley; Kara N. Youngentob; Karen Marsh; Maldwyn J. Evans; Tyrone Lavery; Kita Ashman; Ana Gracanin; David Lindenmayer (PLoS ONE, 2025)
The loss of hollow-bearing trees drives population declines of hollow-dependent species. Disturbances such as wildfire can exacerbate these declines. Artificial structures, like nestboxes, are a commonly used management tool that attempt to offset hollow loss. However, the effectiveness of nestboxes as a conservation strategy is rarely tested within an experimental framework. The endangered southern greater glider ( Petauroides volans) is an obligate hollow-dependent arboreal marsupial that is highly sensitive to wildfire. Southern greater glider populations experienced high mortality and habitat degradation following the 2019/2020 megafires in south-eastern Australia. We established a long-term, landscape-scale experiment to test whether purpose-built nestboxes could assist the post-fire population recovery of the southern greater glider. We installed a total of 234 nestboxes at sites in East Gippsland (north-eastern Victoria) and Tallaganda (southern New South Wales). We matched nestbox sites to control sites. We undertook spotlighting surveys in both study areas and installed camera traps at a subset of nestboxes. We observed southern greater gliders using nestboxes in both regions, with substantially more observations in Tallaganda. These early results did not indicate a significant difference in the relative abundance of southern greater gliders between nestbox and control sites. In Tallaganda, we found more southern greater gliders in areas of lower fire severity. The longer-term outcomes of our study will inform the use of nestboxes as a tool to assist in the recovery of southern greater gliders following disturbance.